Consumerism and Advertisement - Muhammad Abbas (بازیافت, 2021)
Consumerism is an important subject in almost every literary and intelectual discussion all across the board. In the name of consumerism, the third world is being made subserviant to the advanced nations. Advertisement paves the way in this regard. Keeping the trend in view, in this article, it has been analysed that how advertisement marks its impact on the masses and try to make them mere consumers by manipulating them through mass advertisement and how far this manipulation of the public proves successful. Moreover, how man become the slave of the companies and by which meaures one can avoid to become a consumer.